2004
DOI: 10.1037/0022-006x.72.2.304
|View full text |Cite
|
Sign up to set email alerts
|

Using a Human Figure Drawing to Elicit Information From Alleged Victims of Child Sexual Abuse.

Abstract: Ninety 4- to 13-year-old alleged victims of sexual abuse were interviewed by police officers using the National Institute of Child Health and Human Development (NICHD) investigative interview protocol, following which they were shown a human figure drawing and asked a series of questions. The drawing and associated questions elicited an average of 86 new forensically relevant details. They were especially productive with 4- to 7-year-olds, who provided an average of 95 additional details (27% of their total) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 38 publications
2
76
1
6
Order By: Relevance
“…The dynamic nature of the field is demonstrated in the constant changes and improvement in forensic interview models and structures. Especially helpful in the progress has been the research of the team advocating the NICHD Protocol [27,82,[84][85][86][87][93][94][95][96][97][98].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic nature of the field is demonstrated in the constant changes and improvement in forensic interview models and structures. Especially helpful in the progress has been the research of the team advocating the NICHD Protocol [27,82,[84][85][86][87][93][94][95][96][97][98].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the NICHD Protocol researchers have engaged in field research that has demonstrated the "value added" of a human figure drawing [93] and of asking the child to draw a picture of the abuse [94]. In both of these studies, the drawing activity was introduced after verbal inquiry and elicited substantial portions of new information.…”
Section: Use Of Mediamentioning
confidence: 99%
“…The validity of human figure drawing test scores is debated (Gresham, 1993;Motta, Little, & Tobin, 1993a, 1993b, but only with respect to behavioral risk assessment using particular features of the human figure as indicators of disturbed emotions (Aldridge et al, 2004;Bekhit, Thomas, & Jolley, 2005;Lange-Küttner, 1989;ter Laak, de Goede, Aleva, & van Rijswijk, 2005;Thomas & Jolley, 1998). In young children, drawing recognizable human figures requires the ability to follow simple response rules (Riggs, Jolley, & Simpson, 2013).…”
mentioning
confidence: 99%
“…Research has found that drawing per se is not a useful technique to use as a central investigative tool because of the increase in errors (Brown, Pipe, Lewis, Lamb, & Orbach, 2007). It has been recommended that, if drawing is used in interviews, it be used late in the interview when every attempt to verbally elicit reports has been made, and to combine it with open-ended questions (Aldridge, Lamb, Sternberg, Orbach, Esplin, & Bowler, 2004).…”
Section: Discussionmentioning
confidence: 99%